Economic instruments and environmental policy - Helm, Dieter (Economic & Social Studies, 2005)
Environmental resources are scarce and many are getting scarcer. Resource allocation problems abound and recent experience is disheartening. Despite the growing scientific consensus on global warming, action to reduce greenhouse gas emissions has been largely ineffectual. Progress with energy efficiency measures and on renewables has been slow. In the former case, the effect of rising incomes has stimulated demand offsetting on a global level the contribution from technology in widening the gap between economic growth and energy demand. With the prospect of a further 3 billion people this century, and the rapid development of China and India, demand effects will continue to put upward pressure on emissions. The International Energy Agency (IEA) estimate that world energy demand will rise by 1.7 per cent per annum between 2002 and 2030, and CO2 emissions over the period by 60 per cent (IEA, 2004). In the case of renewables, limited progress in Europe will be offset by the decline of nuclear output. Biodiversity loss ? the rate of habitat loss and associated extinctions ? shows no sign of slowing down. In a period which matches the geological extinction episodes, efforts to protect the great repositories of biodiversity ? like the rain forests ? have had little aggregate effect. By the end of the century, much of the Amazon will be gone. These problems have been largely caused by the industrial transformation of the twentieth century, based upon the harnessing of fossil fuels, which helped to facilitate a five-fold increase in population. Correcting them will require a switch from fossil to non-fossil fuel energy sources and the protection of species and habitats. These changes will be costly, and a natural way to make the transition to a more sustainable economy is to use the price mechanism and markets. Economic instruments, correcting for the market failures, are an obvious route forward for environmental policy, harnessing the market to deliver the economic transformation required. Yet the paradox is that economic instruments remain the exception rather than the rule, and their design owes more to politics and vested interests than the guidance which economic theory provides. The toolbox of economics has been largely ignored. The aim of this paper is to restate the arguments for economic instruments, and to explain why this paradox arises by considering the political economy of introducing economic instruments, in particular the role of interest groups, lobbying and capture. Whereas economists ? and environmentalists ? are interested in the substitution effect towards a more environmentally benign economy, political economy is focused on the economic rents from policy and in particular the income effect.
The ESR/DEW Guest Lecture. This paper was an invited presentation at the Nineteenth Annual Conference of the Irish Economic Association in Kilkenny, May 6-8, 2005
Keywords: Environmental policy; Economic instruments; Taxation